Another Killer Industry: A Review of Fake Silk by Paul Blanc. (April 2018) - Berman, Daniel
Rayon, a shiny artificial fabric with the flashy allure of silk, constitutes no danger to consumers. But worker exposure to carbon disulfide, an essential input in rayon manufacture, can drive workers insane and kill them as well. The dangers of carbon disulfide have been known since the middle of the 19th century. Professor Paul Blanc's book traces the social amnesia about the dangers of making rayon and how its production has shifted from wealthy countries in Europe, the United States, and Japan to poorer countries like South Korea and the People's Republic of China. The history of the rayon industry constitutes a metaphor for the lives of millions of people who toil unnoticed at dangerous jobs to support their families and help make life possible and even pleasurable for the luckier ooernes.